Silicon carbon composite material and method for preparation and use thereof
Patent Information
- Application Number
- JP2023530720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-20
- Filing Date
- 2021-07-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-07-19
AI Technical Summary
【0008】 上記に加えて、シリコン炭素複合材料の被覆層の構造により、電解質がコアに入ることを効果的に防止することができ、これにより、SEI膜が繰り返し生成されることが防止されることが可能であり、これにより、リチウムイオンの消費が効果的に減らされ、SiOx粒子の有効部位の減少が減らされ、また、被覆層の構造はコアの不安定要因を減らすように、SiOx粒子によって生成される膨張力をさらに吸収するコアの緩和部として用いられることも可能であり、これにより、シリコン炭素複合材料のエネルギー密度と構造安定性とが確保される。
Smart Images

Figure 0007635380000002 
Figure 0007635380000003 
Figure 0007635380000004
Abstract
Description
[Technical field]
[0001] This application claims priority to Chinese Patent Application No. 202011306499.0, filed with the State Intellectual Property Office of the People's Republic of China on November 20, 2020, and entitled “SILICON CARBON COMPOSITE MATERIAL AND PREPARATION METHOD AND APPLICATION THEREOF,” the entirety of which is incorporated herein by reference.
[0002] The present application relates to the field of secondary battery technology, and in particular to silicon carbon composite materials and methods for preparing and using silicon carbon composite materials. [Background technology]
[0003] Lithium-ion batteries are widely used in household appliances and electric vehicle products due to their advantages of high energy utilization efficiency, environmental friendliness, and high energy density, and have attracted much attention as a key technology for large-scale energy storage systems. In one aspect, with the development of 5G technology, household appliances consume large antenna power and high high-frequency power of batteries, and household appliances have high requirements for battery capacity. In yet another aspect, as pure EVs and hybrid electric vehicles are popularized and government subsidies are gradually reduced, it is important for electric vehicles to rely on their own technical and product advantages to ensure the sustainable and healthy development of the entire industry chain. This places high demands on lithium-ion batteries, and lithium-ion batteries are required to have high energy density and long cycle life. The energy density of lithium-ion batteries is mainly determined by the specific capacity and potential of the positive and negative electrode materials. Graphite as the negative electrode material of conventional lithium-ion batteries has a low theoretical specific capacity (372 mAhg -1), which cannot meet the increasing energy density demands of users for lithium-ion batteries. The theoretical specific capacity of silicon is 4200 mAh / g, making it the material with the highest theoretical gram capacity. Therefore, silicon-based materials are currently one of the most considered anode materials with the greatest potential to replace graphite.
[0004] However, compared to conventional graphite anodes, the use of silicon-based anodes in battery cells is still in its infancy. As a semiconductor material, silicon has an extremely low intrinsic electronic conductivity of 2.52×10 -4 S / m. Therefore, the lithium ion conductivity performance of silicon-based negative electrode materials is poor, which affects the fast charging ability of the battery. In addition, the structural stability of silicon is poor. During charging, when lithium ions are released from the positive electrode and inserted into the silicon material, the silicon material expands and shatters. During discharging, when lithium ions are released from the silicon material, large gaps are formed, so the silicon material shrinks. During continuous charging and discharging of the battery, the expansion and contraction of the silicon-based negative electrode seriously affects the cycle performance and rate performance of the battery. Summary of the Invention
[0005] In the embodiment of the present application, a silicon carbon composite material and the preparation method and use of the silicon carbon composite material are provided. The structure and composition of the silicon carbon composite material are adjusted, which can overcome the defects of the poor stability and poor electrical conductivity of silicon-based materials. In this way, the secondary battery has excellent energy density, and also has excellent cycle performance, rate performance and fast charging performance. [Means for solving the problem]
[0006] In a first aspect of an embodiment of the present application, there is provided a silicon carbon composite material, the silicon carbon composite material comprising a core and a carbon coating layer, at least a portion of a surface of the core is covered by the carbon coating layer; The core is made of carbon substrate and SiO xparticles, the carbon substrate comprising N channels continuously distributed and communicating with the outside, SiO x The particles are packed into the channel, SiO x The particle size is 0.1 nm to 0.9 nm, 0.9≦x≦1.7, and N≧1, where N is an integer; A silicon carbon composite material is provided.
[0007] The silicon carbon composite material of this embodiment of the present application is a core-shell structured silicon carbon composite material, in which the SiO x The particles are primarily used to accomplish lithium ion deintercalation. SiO x The particle size is extremely small, less than 1 nm, so SiO x In order to avoid the particle crushing phenomenon, the SiO x The degree of particle expansion and contraction is also adjusted, which makes it easier to ensure the structural stability of the silicon carbon composite material. x As the particles fill the channels of the carbon substrate, SiO x The carbon matrix surrounding the particles is SiO x It also acts as a buffer against the expansion generated by the particles, which further improves the structural stability of the silicon carbon composite. In addition to the above, the structure of the carbon matrix is continuous and the SiO x The small particle size ensures effective transfer of lithium ions and electrons, giving the silicon carbon composite excellent electrical conductivity.
[0008] In addition to the above, the structure of the coating layer of the silicon carbon composite can effectively prevent the electrolyte from entering the core, which can prevent the repeated generation of the SEI film, which can effectively reduce the consumption of lithium ions and reduce the SiO x The reduction in the effective sites of the particles is reduced, and the structure of the coating layer is such that the instability factor of the core is reduced. xIt can also be used as a buffer for the core to further absorb the expansion forces generated by the particles, thus ensuring the energy density and structural stability of the silicon carbon composite.
[0009] Therefore, the silicon carbon composite material of this embodiment of the present application is SiO x The use of particles not only achieves high energy density, but also has excellent structural stability and electrical conductivity, so that the secondary battery exhibits balanced electrical performance, and not only has high energy density, but also has excellent cycle performance, rate performance and fast charging performance.
[0010] In a possible implementation, the mass percentage of the carbon substrate is 10% to 40% based on the mass of the core. By limiting the mass percentage of the carbon substrate in the core, the balance of the energy density, cycle performance, rate performance and fast charging performance of the secondary battery can be optimized to a considerable extent.
[0011] In a possible implementation, the specific surface area of the carbon substrate is 800 m 2 / g~1400m 2 / g. The carbon substrate has a channel structure, and the large specific surface area of the carbon substrate indicates that the number of channels in the carbon substrate is large, the size is small, and the distribution density is high. Therefore, a large amount of SiO x The particles are packed into the channels and uniformly distributed at high density on the surface of the carbon substrate. x The uniform particle distribution not only facilitates the improvement of the energy density of the secondary battery, but also promotes lithium ion intercalation and ensures the fast charging capability of the secondary battery. In addition, the large number of reduced-size channels allows the adjacent SiO x This makes it easier to have a continuous carbon substrate between the particles. This allows the carbon substrate to be x It is possible to further ensure that the expansion force of the particles is alleviated, and SiO xNot only can it improve the structural stability of the particles, but it can also prevent the lithium ions that enter the core during the charging process from entering the SiO x It can also be introduced into particles more quickly, and SiO x Lithium ions released from the particles can also be quickly guided out of the core, thereby further improving the excellent rate and cycle performance of the secondary battery.
[0012] In a possible realization, a silicon carbon composite with a specific surface area of 5 m 2 / g~20m 2 / g. This specific surface area indicates that the carbon coating layer on the surface of the silicon carbon composite is dense. Therefore, the electrolyte is effectively prevented from passing through the carbon coating layer into the core, and the SiO x It is possible to avoid the repeated formation of the SEI film caused by the crushing and disintegration of particles, which effectively suppresses the consumption of lithium ions and reduces the amount of SiO 2 used for lithium ion intercalation. x Nearly all of the available sites of the particles can be reliably preserved, thereby optimizing both the cycle and rate capabilities of the secondary battery to a great extent.
[0013] In a possible implementation, the Raman spectrogram of the carbon substrate has 0.8≦ID / IG≦1.5. This ratio indicates that the carbon substrate has a high degree of graphitization in the case of the silicon carbon composite of this embodiment of the present application, which is more conducive to electronic conduction. In addition to the above, SiO x As the particles expand, SiO x Slippage of the highly graphitized carbon substrate also occurs so that good relief of the expansion stresses of the particles is achieved.
[0014] In a possible implementation, the nuclear magnetic resonance spectrum of the silicon carbon composite material comprises a Si-C peak and a Si-O peak, and the intensity of the Si-O peak is I Si-O Intensity of Si-C peaks vs. I Si-CThe ratio of is less than 0.05. Unlike conventional silicon oxygen carbon materials that have a large number of Si-C bonds that affect the electrical conductivity of the material, the silicon carbon composite material of the present application has a very small number of Si-C bonds, so the carbon substrate has better electrical conductivity, which allows the high-speed charging capability of the secondary battery to be implemented.
[0015] In a possible embodiment, the thickness of the carbon coating layer is 5 nm to 20 nm, and the carbon atom interlayer spacing d002 of the carbon coating layer is 0.3354 nm to 0.34 nm. The graphitization degree of the coating layer is high. Even if the coating layer is squeezed due to the deformation of the core, the coating layer can release the stress through the slip of the interlayer, reducing the probability of the coating layer being destroyed, and can also increase the protective strength of the coating layer against the core, thereby further ensuring the cycle performance and rate performance of the secondary battery.
[0016] In a possible implementation, the silicon carbon composite further comprises at least one of the elements N, P, B, Cl, Br and I. Doping with these different elements can improve the electrical conductivity of the silicon carbon composite, which can further improve the rate performance of the secondary battery.
[0017] In a possible implementation, the particle size of the silicon carbon composite material is 50 nm to 2 μm. Based on different particle sizes, the silicon carbon composite material of this embodiment of the present application can be used in different application scenarios. For example, the silicon carbon composite material with small particle size can be used as the base material of the negative electrode active material for further processing, and the silicon carbon composite material with large particle size can be directly used as the negative electrode active material, and can be mixed with conductive additives, binders, etc. to prepare the active functional layer of the negative electrode plate.
[0018] In a possible implementation, the silicon carbon composite material is (1) stirring an aqueous solution of a trimethoxysilane compound under alkaline conditions to make the system turbid, and collecting precursor particles; (2) A process for sintering precursor particles to obtain a silicon carbon composite material, the sintering temperature is 900°C to 1200°C, and the sintering duration is 1 hour to 10 hours. The compound is prepared using a method comprising the steps of:
[0019] In a second aspect of an embodiment of the present application, there is provided a method for preparing a silicon carbon composite material, comprising the steps of: (1) stirring an aqueous solution of a trimethoxysilane compound under alkaline conditions at 25°C to 85°C to make the system turbid, and collecting precursor particles; (2) carrying out a sintering process on the precursor particles to obtain a silicon carbon composite material, the sintering temperature being 1000°C to 1200°C, and the sintering duration being 1 hour to 10 hours; Including, The silicon carbon composite material includes a core and a carbon coating layer, and at least a portion of a surface of the core is covered with the carbon coating layer; The core is made of carbon substrate and SiO x particles, the carbon substrate comprising N channels communicating with the outside, SiO x The particles are packed into the channel, SiO x The particle size is 0.1 nm to 0.9 nm, and 0.9≦x≦1.7; A method is provided.
[0020] By using this preparation method, it is possible to obtain a silicon carbon composite material through preparation, which not only facilitates the secondary battery to have high energy density, but also allows the secondary battery to have excellent cycle performance, rate performance and high-speed charging performance.
[0021] In a possible implementation, in step (1), ammonia water having a volume concentration of 0.6% to 15% is added to an aqueous solution of a trimethoxysilane compound so that the pH of the system is 8 to 13.
[0022] In a possible realisation, the aqueous solution of trimethoxysilane compound has a volume concentration of the trimethoxysilane compound of 0.4% to 5%.
[0023] The above process parameters are conducive to dissolving the raw materials and ensuring that the spherical silsesquioxane precursor particles have an appropriate size.
[0024] In a possible implementation, the temperature ramp rate of the sintering process is 1° C. / min to 10° C. / min. By adjusting the temperature ramp procedure, the graphitization degree of the carbon substrate can be improved.
[0025] In a possible implementation, after step (1), the method further comprises the step of providing a carbon source in the system for carbon coating.
[0026] In a possible implementation, the carbon coating is performed using a deposition reaction, the temperature of the deposition reaction being between 700°C and 1200°C.
[0027] The above carbon coating process parameters not only facilitate the formation of the carbon coating layer of the silicon carbon composite, but also allow the formation of SiO x It is also possible to further ensure a predetermined size of the particles, which results in SiO x An increase in particle size is avoided.
[0028] In a possible implementation, the trimethoxysilane compound is trimethoxysilane, methyltrimethoxysilane, N-trimethoxypropylsilane, N-trimethoxyoctylsilane, 3-aminopropyltrimethoxysilane, 3-1-[3-(trimethoxysilyl)propyl]urea, N-dodecyltrimethoxysilane, (3-chloropropyl)trimethoxysilane, (3-phobyl ... propyltrimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, trimethoxybenzenesilane, vinyltrimethoxysilane, and 3-iodophenyltrimethoxysilane.
[0029] In a third aspect of an embodiment of the present application, there is provided an electrode plate, the electrode plate comprising the silicon carbon composite material of the first aspect or obtained using the preparation method of the second aspect.
[0030] The silicon carbon composite material of the first embodiment and the silicon carbon composite material obtained in the second embodiment have high energy density, excellent structural stability and electrical conductivity, so that the electrode plate can exhibit excellent performance. For example, the electrode plate can be a negative electrode plate. In particular, the electrode plate has a stable structure, the active layer is not easily detached from the current collector, and the electrode plate has excellent electrical conductivity, so that the electrode plate can further implement a large capacity of the secondary battery.
[0031] In a fourth aspect of the embodiment of the present application, there is provided a secondary battery, the secondary battery including the electrode plate of the third aspect.
[0032] Since the above electrode plate is used in the secondary battery of this embodiment of the present application, the secondary battery has a large capacity and also has excellent performance in cycle performance, rate performance and high-speed charging performance.
[0033] In a fifth aspect of the present embodiment, there is provided an electronic device, wherein a driving source or an energy storage source of the electronic device is the secondary battery according to the fourth aspect.
[0034] Since electronic devices are powered or store energy using the secondary batteries, the battery life and electronic device life are excellent, and the user experience is excellent. [Brief description of the drawings]
[0035] [Figure 1] 1 is a schematic diagram of a structure of an electronic device according to an embodiment of the present application; [Diagram 2] FIG. 2 is a schematic diagram of a separated structure of an electronic device according to an embodiment of the present application. [Figure 3a] FIG. 2 is a SEM diagram of the overall morphology and microstructure of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 3b] FIG. 2 is a high resolution HAADF phase diagram of a cross section of a fractured area of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 3c] FIG. 1 is a TEM diagram of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 3d] FIG. 3b is a partial enlarged view of the coating layer of FIG. 3c. [Figure 3e] FIG. 2 is a high-resolution STEM image of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 3f] FIG. 2 is a SEM with EELS surface scan of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 3g] FIG. 2 is a SEM with EELS surface scan of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 3h] FIG. 2 is a SEM with EELS surface scan of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 4] 29Si magic angle spinning nuclear magnetic resonance (MAS NMR) spectrum of the silicon carbon composite material according to embodiment 1 of the present application; [Figure 5a] FIG. 2 is a TEM image of the carbon substrate taken after etching of the silicon carbon composite material according to embodiment 1 of the present application. [Figure 5b] 1 is a Raman spectrogram of a carbon substrate obtained after etching of a silicon carbon composite material according to embodiment 1 of the present application; [Figure 5c] 1 shows N2 adsorption and desorption curves of a silicon carbon composite material according to embodiment 1 of the present application before and after etching. [Figure 5d] 1 is a N2 adsorption and desorption aperture distribution curve of a silicon carbon composite material according to embodiment 1 of the present application before and after etching; [Figure 5e] 1 is a CO2 aperture distribution curve of a carbon substrate obtained after etching a silicon carbon composite material according to embodiment 1 of the present application; [Figure 5f] 1 is an XPS spectrogram of a silicon carbon composite material according to embodiment 1 of the present application. [Figure 6] FIG. 2 is a schematic diagram of the overall morphology and microstructure of a silicon carbon composite material according to embodiment 2 of the present application. [Figure 7a] FIG. 2 is a scanning electron microscope view of the morphology of a silicon oxygen carbon negative electrode material according to Comparative Example 1 of the present application. [Figure 7b] FIG. 2 is a TEM image of the inside of a silicon oxygen carbon negative electrode material according to Comparative Example 1 of the present application. [Figure 8a] FIG. 1 is a high resolution HAADF phase diagram of a cross section of a fractured area of a silicon carbon composite material according to Comparative Example 2 of the present application. [Figure 8b] FIG. 11 is a TEM image of the carbon substrate obtained after etching of the silicon carbon composite material according to Comparative Example 2. [Figure 9] 29Si magic angle spinning nuclear magnetic resonance (MAS NMR) spectrum of the silicon carbon composite material of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] The terms used in the implementation of the present application are only used to describe specific embodiments of the present application, while not intended to limit the present application. Hereinafter, the implementation of the embodiment of the present application will be described in detail with reference to the accompanying drawings.
[0037] In order to overcome the deficiency of silicon-based materials in terms of their poor structural stability, people skilled in the art have used several methods to improve silicon-based materials.
[0038] For example, the article "Crystalline-amorphous core-shell silicon nanowires for high capacity and high current battery electrodes. Nano Lett., 2009, 491-495" describes a core-shell design of silicon nanowires for use in high-power, long-life lithium battery electrodes. "Silicon crystalline core-amorphous shell nanowires" are grown directly on stainless steel collectors through a simple one-step synthesis. Due to the difference in lithiation potential between amorphous silicon and crystalline silicon, an electrochemically active amorphous silicon shell can be selected instead of the crystalline silicon core. Thus, the crystalline silicon core serves as a stable mechanical support and an effective conductive path, while the amorphous shell stores Li+ ions. The core-shell nanowires have a high charge storage capacity of about 1000mAh / g and a capacity retention rate of about 90% for 100 cycles. They also show excellent electrochemical performance at high charge and discharge rates (about 20 times that of carbon at a rate of 6.8A / g 1 hour). In the paper “A pomegranate-inspired nanoscale design for large-volume change lithium battery anodes, Nature Nanotech, 2014, 9, 187-192,” a silicon anode with a hierarchical structure inspired by the structure of a pomegranate is proposed. A single silicon nanoparticle is wrapped by an electrically conductive carbon layer, which leaves enough space for expansion and contraction after lithiation and lithium extraction. The composite nanoparticle is then completely wrapped in a micron-level bag and wrapped by a thick carbon layer that serves as a barrier to the electrolyte. This hierarchical arrangement keeps the solid electrolyte interphase stable and spatially limited, and therefore has excellent reusability (reusability with 97% capacity retention after 1000 cycles).Although the nanomaterial is structurally designed to reduce the volume expansion of silicon and provides silicon with an excellent physical barrier to protect it from direct contact with the electrolyte, the internal space of the material has many designs and a complex structure, which is problematic in practical applications, such as applications with a large specific surface area or low tap density. In addition, the structural stability of silicon nanowires with core-shell structure and nanosilicon particles with egg yolk-shell structure against external pressure is poor, and deformation and particle destruction are likely to occur during the rolling process of the actual processing of the electrode plate. As a result, the electrolyte comes into direct contact with the internal silicon material, causing many side reactions, which affect the performance of the battery cell, and it is difficult to reproduce extremely high performance in this article.
[0039] CN102214823A, CN106816594A, etc. disclose a silicon-silicon oxide complex structure, in particular, a structure in which silicon with a particle size of 0.5 nm to 50 nm is dispersed in silicon oxide at the atomic level and / or in a microcrystalline state. In order to further improve the initial efficiency of silicon monoxide, lithium is supplemented based on the above, and a structure in which silicon with a particle size of 1 nm to 50 nm is dispersed in silicate and silicon oxide at the atomic level and / or in a microcrystalline state is formed. In particular, nanosilicon is uniformly dispersed in silicon oxide and / or silicate. After lithium is inserted into the material, a chemically inert lithium oxide and silicate network is formed by silicon oxide, which can be used as a relaxation layer to reduce the stress generated by the expansion of nanocrystalline silicon. In this material structure, nanosilicon is SiO x and / or silicate network. Although the stress generated by the expansion after lithium is inserted into silicon can be well absorbed, the electronic conductivity of the network is very low, which affects the fast charging ability.
[0040] CN107093711B etc. contains monodispersed SiO x Monodisperse SiO2 improves the structural stability of -C composite microspheres x The macroscopic preparation method of SiO-C composite microspheres and the structure and performance of the microspheres are disclosed. However, in addition to the organosilicone source, a phenol source and formaldehyde are polycondensed, and the resulting product is used as an additional carbon source in the material synthesis process. Therefore, a large number of carbon components are inserted into the material, which affects the lithium intercalation capacity and the initial efficiency of the material. In addition, there are a large number of Si-C bonds in the material, and therefore, the SiO x The phase separation between the Si and carbon networks cannot be completely achieved. The large number of Si-C bonds affects the internal electrical conductivity of the material, and the electrochemical activity of Si connected to C atoms is very low, which has a negative impact on the lithium intercalation capacity and fast charging ability.
[0041] Based on the above deficiencies, a first aspect of an embodiment of the present application provides a silicon carbon composite material. The silicon carbon composite material includes a core and a carbon coating layer, and at least a part of the surface of the core is covered by the carbon coating layer. The core is made of a carbon substrate and SiO x particles, the carbon substrate comprising N channels continuously distributed and communicating with the outside, SiO x The particles are packed into the channels. SiO x The size of the particles is 0.1 nm to 0.9 nm, 0.9≦x≦1.7, and N≧1, where N is an integer.
[0042] The silicon carbon composite material of this embodiment of the present application has a core-shell structure. The core is a carbon substrate and a nanotube having a size of 0.1 nm to 0.9 nm (SiO x The maximum size of the particles is the SiO x The silicon carbon composite material of this embodiment of the present application includes all SiO x The particles are located inside the channels of the carbon substrate, and the SiO xIt should be noted that the degree of filling of particles is not limited in this embodiment of the present application, and the degree of filling may be less than 100%. The channel in this embodiment of the present application is a containing space with a certain depth, similar to the shape of a worm, communicating with the outside, the carbon substrate is continuously distributed, and is a carbon structure with a certain volume.
[0043] SiO is a silicon-based material with a high specific capacitance. x The presence of the particles in the core can greatly improve the energy density of the silicon carbon composite, so that the energy density of secondary batteries containing the silicon carbon composite is high. x In order to overcome the defect of low structural stability of the particles, the SiO x The size of the particles is extremely small, only 0.1 nm to 0.9 nm. Therefore, the lithium ion intercalation produces SiO x Even if the volume of the particles expands, SiO x The degree of particle expansion is extremely low, and the phenomenon of collapse and crushing does not occur fundamentally. In addition, SiO x The carbon substrate that provides the space for the particles is SiO x Not only can it mitigate the expansion of the particles to some extent, but it can also prevent the adjacent SiO x It is also possible to effectively separate particles, and the SiO x This avoids the problem of excessively high particle expansion, thereby reducing the SiO x The structural stability of the particles is further maintained. Therefore, the silicon carbon composite material of this embodiment of the present application can overcome the defects of silicon-based materials that have poor structural stability and are easily expanded.
[0044] In addition to the above, SiO x By reducing the particle size, SiO x The lithium ion transfer path inside the particle is also shortened, and the diffusion rate of lithium ions is improved. In addition, the intercalated lithium ions and SiO xThe production of lithium oxide during particle reaction also facilitates the improvement of ionic and electrical conductivity, while the continuously distributed carbon matrix in the core is effectively equivalent to a continuous ion- and electrical-conducting network, and SiO x Not only can it provide a pathway for lithium ions to be inserted into the particles, but it can also quickly output the generated electrons to an external circuit, so the silicon carbon composite material of this embodiment of the present application has excellent electrical conductivity.
[0045] Since silicon-based materials have the defect of being easily expanded and crushed, when the electrolyte contacts the silicon-based material, the specific surface of the silicon-based material is continuously increased as the silicon-based material is repeatedly expanded and crushed. As a result, a lot of electrolyte is consumed to repeatedly form the SEI film on the surface of the silicon-based material. This not only results in a large consumption of lithium ions, but also causes safety problems due to increased gas generation. In contrast, in the silicon carbon composite material of this embodiment of the present application, the carbon coating layer covers at least a part of the surface of the core as a housing structure, and can be used as a barrier to prevent the electrolyte from penetrating the core, reducing the contact area between the electrolyte and the core, especially the electrolyte and SiO x The contact area with the particles is reduced, which avoids high lithium loss and excessive gas generation.
[0046] According to the silicon carbon composite material of this embodiment of the present application, the core is made of SiO x Contains particles, SiO x The particle size is adjusted, and SiO x A continuous carbon matrix is placed around the particles, which allows for easy expansion and SiO x The defect of poor electrical conductivity of the particles is overcome, and the SiO xThe adverse impact of particles is avoided to a great extent. In addition, the carbon coating layer covers the surface of the core, which further reduces the contact area between the silicon carbon composite and the electrolyte, thereby reducing the lithium loss and gas production during the long-term cycle process of the secondary battery, thereby ensuring the cycle performance and safety performance of the secondary battery. Therefore, the silicon carbon composite material of the present application not only allows the secondary battery to have high energy density, but also ensures the cycle performance, rate performance and fast charging performance of the secondary battery, so that the secondary battery has a more balanced and excellent electrical performance.
[0047] The content of the carbon base material in the core as a component of the core may be 10% to 40% by mass. x It can be seen that the mass percentage of the carbon substrate in the core shows an inverse trend. Specifically, when the mass percentage of the carbon substrate in the core increases, the SiO x When the mass percentage of the particles decreases, or when the mass percentage of the carbon substrate in the core decreases, the SiO x The mass percentage content of particles increases. SiO x The large mass content of particles indicates a significant improvement in the energy density of secondary batteries, but the resulting SiO x The particle expansion and aggregation phenomena are also very serious. Therefore, if the mass percentage of the carbon substrate in the core is 10% to 40%, the SiO x The relaxation and separation effects of the carbon substrate on the particles can be effectively achieved, and the SiO x The good and bad impacts brought by the particles at the same time are balanced, thereby ensuring the cycle performance and rate performance of the secondary battery. In addition, the content in mass percentage of the carbon substrate can ensure that the silicon carbon composite has excellent electrical conductivity, which can further improve the fast charging ability of the secondary battery.
[0048] In a possible implementation, the specific surface area of the carbon substrate is 800 m 2 / g~1400m 2 / g, which indicates that a large number of channels are distributed on the surface of the carbon substrate. x It can be seen that the number of particles is large. Therefore, the SiO x The distribution density of the particles is high, which allows the SiO x Lithium ions can be more easily inserted into the surface of the particles, accelerating the intercalation rate of lithium ions, which promotes high-speed charging of secondary batteries. In addition, the large number of channel structures also contributes to the carbon substrate being made of SiO x The particles are surrounded by SiO x The particle distribution is independent, and SiO x By reducing the particle aggregation phenomenon, the structural stability of the silicon carbon composite material is further improved, which means that the cycle performance and rate performance of the secondary battery are ensured.
[0049] Furthermore, the specific surface area of the silicon carbon composite material of this embodiment of the present application is 5 m 2 / g~20m 2 / g. The specific surface area of the silicon carbon composite is small, which indicates that the surface structure of the silicon carbon composite is dense. This not only reduces the contact area between the electrolyte and the surface of the silicon carbon composite, thereby avoiding the consumption caused by the formation of a large area SEI film by the electrolyte, but also effectively prevents the electrolyte from entering the core, thereby reducing the amount of SiO x The excessive consumption of electrolyte caused by particle swelling and crushing is prevented, and therefore the specific surface area of the silicon carbon composite material facilitates improving the cycle performance and rate performance of the secondary battery by reducing lithium loss.
[0050] In addition to the above, the dense surface of the silicon carbon composite reduces contact between the core and the electrolyte, allowing other compounds in the electrolyte to be transported to the SiO xTherefore, in this embodiment, SiO x The particles have more available sites for intercalation of lithium ions, which allows the secondary battery to exhibit sufficient cycle and rate capabilities.
[0051] The excellent electrical conductivity of the carbon substrate and SiO x In order to further ensure the relaxation effect of the carbon substrate on the particles, a carbon substrate with a high degree of graphitization can be selected. In particular, the Raman spectrogram of the carbon substrate is 0.8≦ID / IG≦1.5. A carbon substrate with ID / IG in this range is SiO x The inventors have found through research that when subjected to stress generated by particle expansion, a certain degree of slip in the interlayer spacing can not only effectively release the stress, but also prevent damage to the carbon coating layer.
[0052] In addition, when the secondary battery uses various positive electrode active materials, electrolytes or separators, the high-speed charging performance of the secondary battery is affected. Therefore, in summary, when the positive electrode active materials, electrolytes, separators, etc. are various as described above, it can be fundamentally ensured that the electrical conductivity of the carbon substrate is outstanding when the ID / IG of the carbon substrate is 0.8≦ID / IG≦1.5, which makes it easy to optimize the high-speed charging performance of the secondary battery to the maximum extent.
[0053] In addition to ensuring the degree of graphitization of the carbon substrate, in a possible implementation, the silicon carbon composite material of this embodiment of the present application is different from conventional silicon oxygen carbon materials, in which the electrical conductivity of the material is limited due to the presence of a large number of Si-C bonds. The nuclear magnetic resonance spectrum of the silicon carbon composite material of this embodiment of the present application includes a Si-C peak and a Si-O peak, and the intensity of the Si-O peak I Si-O Intensity of Si-C peaks vs. I Si-C The ratio of is less than 0.05. The core of the silicon carbon composite material contains silicon and carbon elements, but the I Si-C / I Si-Ois very low, which indicates that the core carbon matrix is fundamentally independent and does not have a strong bonding relationship with silicon element, so that the excellent electrical conductivity of carbon element is further ensured, so that the secondary battery can exhibit more outstanding fast charging performance.
[0054] In a possible implementation, the carbon coating layer may have a thickness of 5 nm to 20 nm and a carbon atom interlayer spacing d002 of 0.3354 nm to 0.34 nm.
[0055] As mentioned above, the carbon coating layer of the silicon carbon composite material of this embodiment of the present application is mainly used to cut off the contact between the electrolyte and the core, so as to avoid excessive lithium loss affecting the cycle performance and rate performance of the secondary battery. In particular, the carbon coating layer with the above parameters can effectively cut off the contact between the electrolyte and the core, and when the core expands, the carbon atom interlayer spacing d002 can ensure that the carbon coating layer can effectively absorb the expansion force and release the expansion force through the slip of the interlayer, and the SiO x This avoids the phenomenon that excessive expansion of the particles may destroy the carbon coating layer, and further reduces the possibility that the electrolyte may come into contact with the core, thereby making it easier to maintain the cycle performance and rate performance of the secondary battery.
[0056] In addition to the elements Si, O and C, the silicon carbon composite material of this embodiment of the present application also contains at least one of the foreign elements, such as N, P, B, Cl, Br and I. In particular, the above foreign elements may be present in the raw materials for preparing the silicon carbon composite material, so that the silicon carbon composite material is doped with the foreign elements. SiO x Specific doping sites are located on the particles and / or carbon substrate. Doping with different elements facilitates improving the electrical conductivity of silicon carbon composites, thereby improving the fast charging and rate capabilities of secondary batteries.
[0057] In a specific use process, the silicon carbon composite material of this embodiment of the present application can be processed as required as a substrate of an electrode active material by using another process, or can be directly used as an electrode active material and mixed with a conductive agent, etc., to prepare an active functional layer of an electrode plate. In this embodiment of the present application, the particle size of the silicon carbon composite material is 50 nm to 2 μm, and the above use scenarios can be implemented by selecting silicon carbon composite materials with various particle sizes. Taking the preparation of a negative electrode plate as an example, in particular, silicon carbon composite materials with small particle sizes are more easily used as a substrate of a negative electrode active material for further processing, and silicon carbon composite materials with large particle sizes can be directly used as a negative electrode active material.
[0058] In a possible implementation, the silicon carbon composite material of this embodiment of the present application comprises: (1) A process of stirring an aqueous solution of a trimethoxysilane compound under alkaline conditions to make the system turbid, and collecting precursor particles; (2) A process for obtaining a silicon carbon composite material by sintering precursor particles, the sintering temperature is 900°C to 1200°C, and the sintering time is 1 hour to 10 hours. The compound is prepared using a method comprising the steps of:
[0059] In this embodiment, the silicon carbon composite material having the above structure is obtained by using trimethoxysilane compound as raw material and processing such as melting and sintering.
[0060] The aqueous solution of trimethoxysilane compound in step (1) can be prepared after adding trimethoxysilane compound to water and stirring for 10 to 30 minutes. In a possible implementation, the volume concentration of the aqueous solution of trimethoxysilane compound is 0.4% to 5%.
[0061] The specific type of trimethoxysilane compound is not limited in this embodiment of the present application.For example, the trimethoxysilane compound may be selected from at least one of trimethoxysilane, methyltrimethoxysilane, N-trimethoxypropylsilane, N-trimethoxyoctylsilane, 3-aminopropyltrimethoxysilane, 3-1-[3-(trimethoxysilyl)propyl]urea, N-dodecyltrimethoxysilane, (3-chloropropyl)trimethoxysilane, (3-phobylpropyl)trimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, trimethoxybenzenesilane, vinyltrimethoxysilane and 3-iodophenyltrimethoxysilane, etc.When the trimethoxysilane compound is selected from a plurality of compounds, the ratio of the compounds is not limited in this embodiment of the present application.
[0062] It can be seen that by selecting the trimethoxysilane compound, it is possible to carry out doping of different elements in the silicon carbon composite material and adjustment of the mass content of the carbon substrate in the silicon carbon composite material.
[0063] The temperature range of the above implementation step (1) is broad and only needs to be adjusted to be roughly above 0°C and below 100°C (inclusive), and even between 25°C and 85°C. In the preparation process, the size of the precursor particles can be adjusted by adjusting the temperature in step (1). In particular, the temperature selection has a great impact on the size of the precursor particles, and the size of the precursor particles decreases gradually with increasing temperature.
[0064] By stirring the aqueous trimethoxysilane solution under alkaline conditions, trimethoxysilane is hydrolyzed to form a white emulsion. Stirring is continued, and when the color of the white emulsion does not change, stirring is stopped. After static aging for a while, filtration is performed to collect the precursor particles. The precursor is especially a spherical silsesquioxane precursor. Usually, the period of continuous stirring and static aging is 0.5 hours to 24 hours.
[0065] Being alkaline in step (1) means that the pH environment of the system is in the range of 8 to 13. In a possible implementation, the alkaline environment of the system may be implemented by adding ammonia water to the trimethoxysilane aqueous solution. The inventors have found through research that the concentration of ammonia water has a significant impact on the size of the precursor particles, and when the volume concentration of ammonia water is 0.6% to 15%, the size of the precursor particles can be adjusted to be 400 nm to 600 nm. In this range, with the increase in the concentration of ammonia water, the size of the precursor particles tends to decrease first and then stabilize.
[0066] In step (2), the collected precursor particles are sintered at 1000° C. to 1200° C. for 1 to 10 hours to obtain a silicon carbon composite material. Before sintering, the precursor particles may be washed with ethanol and dried.
[0067] During the sintering process at 1000°C to 1200°C, the C=C groups of the precursor particles are dehydrogenated and carbonized, and then connected to form a continuous carbon matrix, which results in the formation of SiO x is SiO with a size of 0.1 nm to 0.9 nm. x Sectioned into particles, SiO x The particles are loaded into the carbon substrate. In addition, the carbon substrate is also formed after the Si-C bonds of the precursor particles are broken. In addition, the high temperature sintering and carbonization process also causes the light carbon in the precursor particles to flow to the surface of the particles and be carbonized to form a carbon coating layer, thereby obtaining a silicon carbon composite material. The inventors have found that in the sintering process for 1 hour to 10 hours, the graphitization degree of the carbon substrate is affected to different degrees as the sintering time increases.
[0068] In a second aspect of the embodiment of the present application, (1) stirring an aqueous solution of a trimethoxysilane compound under alkaline conditions to make the system turbid, and collecting precursor particles; (2) sintering the precursor to obtain a silicon carbon composite material, the temperature of the sintering is 900°C to 1200°C, and the duration of the sintering is 1 hour to 10 hours; Including, The silicon carbon composite material includes a core and a carbon coating layer, and at least a portion of a surface of the core is covered with the carbon coating layer; The core is made of carbon substrate and SiO x particles, the carbon substrate includes N channels communicating with the outside, the channels including SiO x The particles are packed SiO x The particle size is 0.1 nm to 0.9 nm, and 0.9≦x≦1.7; A method for preparing a silicon carbon composite material is provided.
[0069] In this embodiment of the present application, the silicon carbon composite material having the above structure is obtained by using trimethoxysilane compound as raw material and processing such as dissolution, sintering, etc. The silicon carbon composite material overcomes the defects of silicon-based materials, such as poor structural stability and poor electrical conductivity, and can balance the cycle performance, rate performance and fast charging performance of the secondary battery when the energy density of the secondary battery is improved.
[0070] The aqueous solution of trimethoxysilane compound in step (1) can be prepared after adding trimethoxysilane compound to water and stirring for 10 to 30 minutes. In a possible implementation, the volume concentration of the aqueous solution of trimethoxysilane compound is 0.4% to 5%.
[0071] The specific type of trimethoxysilane compound is not limited in this embodiment of the present application.For example, the trimethoxysilane compound may be selected from at least one of trimethoxysilane, methyltrimethoxysilane, N-trimethoxypropylsilane, N-trimethoxyoctylsilane, 3-aminopropyltrimethoxysilane, 3-1-[3-(trimethoxysilyl)propyl]urea, N-dodecyltrimethoxysilane, (3-chloropropyl)trimethoxysilane, (3-phobylpropyl)trimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, trimethoxybenzenesilane, vinyltrimethoxysilane and 3-iodophenyltrimethoxysilane, etc.When the trimethoxysilane compound is selected from a plurality of compounds, the ratio of the compounds is not limited in this embodiment of the present application.
[0072] It can be seen that by selecting the trimethoxysilane compound, it is possible to carry out doping of different elements in the silicon carbon composite material and adjustment of the mass content of the carbon substrate in the silicon carbon composite material.
[0073] In the prior art, alcohol additives are usually added to the system to adjust the hydrolysis reaction of silane compounds.In order to reduce cost, simplify the process and improve the environmental compatibility of material synthesis, this embodiment of the present application uses an alcohol-free hydrolysis method, and trimethoxysilane aqueous solution is stirred under alkaline conditions, which not only promotes the dissolution of trimethoxysilane, but also allows the size of precursor to be adjusted by temperature control.
[0074] In this embodiment of the present application, the temperature range of the above-mentioned implementation step (1) is broad and only needs to be adjusted to be roughly above 0°C and below 100°C (inclusive), and even 25°C to 85°C. In the preparation process, the size of the precursor particles can be adjusted by adjusting the temperature in step (1). In particular, the temperature selection has a great impact on the size of the precursor particles, and the size of the precursor particles decreases gradually with the increase of temperature.
[0075] By stirring the aqueous trimethoxysilane solution under alkaline conditions, trimethoxysilane is hydrolyzed to form a white emulsion. Stirring is continued, and when the color of the white emulsion does not change, stirring is stopped. After static aging for a while, filtration is performed to collect the precursor particles. The precursor is especially a spherical silsesquioxane precursor. Usually, the period of continuous stirring and static aging is 0.5 hours to 24 hours.
[0076] Being alkaline in step (1) means that the pH environment of the system is in the range of 8 to 13. In a possible implementation, the alkaline environment of the system may be implemented by adding ammonia water to the trimethoxysilane aqueous solution. The inventors have found through research that the concentration of ammonia water has a significant impact on the size of the precursor particles, and when the volume concentration of ammonia water is 0.6% to 15%, the size of the precursor particles can be adjusted to be 400 nm to 600 nm. In this range, with the increase in the concentration of ammonia water, the size of the precursor particles tends to decrease first and then stabilize.
[0077] In step (2), the collected precursor particles are sintered at 1000° C. to 1200° C. for 1 to 10 hours, after which the silicon carbon composite material is obtained. Before sintering, the precursor particles may be washed with ethanol and dried.
[0078] In the sintering process, the C=C groups of the precursor particles are dehydrogenated and carbonized, and connected to form a continuous carbon matrix, which results in the formation of SiO x is SiO with a size of 0.1 nm to 0.9 nm. x Sectioned into particles, SiO x The particles are loaded into the carbon substrate. In addition, the carbon substrate is also formed after the Si-C bonds of the precursor particles are broken. In addition, the high temperature sintering and carbonization process also causes the light carbon in the precursor particles to flow to the surface of the particles and be carbonized to form a carbon coating layer, thereby obtaining a silicon carbon composite material. The inventors have found that in the sintering process for 1 hour to 10 hours, the graphitization degree of the carbon substrate is affected to different degrees as the sintering time increases.
[0079] The sintering process needs to be carried out in an inert / reducing protective atmosphere, including but not limited to one or more of N2, Ar, and H2. In a possible implementation, the sintering process may be carried out in a high temperature furnace.
[0080] In a specific sintering process, the precursor particles can be placed in a high-temperature furnace, and the precursor particles are gradually heated to a target temperature by setting a temperature rise procedure (temperature rise rate), and then the sintering process is carried out for 1 hour to 10 hours. In a possible implementation, when the temperature rise rate of the sintering process is 1°C / min to 10°C / min, a more dense and continuous carbon substrate is formed, which promotes the conduction of lithium ions.
[0081] Furthermore, after step (1), the carbon content in the carbon coating layer on the surface of the core can be further adjusted by providing a carbon source in the system. In particular, the operation of providing the carbon source can be performed before step (2), during step (2), or after step (2). The carbon source can be, for example, at least one of an alkane, an alkene, an alkyne, and benzene. In a possible implementation, adjusting the carbon content of the carbon coating layer on the surface of the core by chemical vapor deposition facilitates improving the graphitization degree of the carbon coating layer. In particular, the temperature of the chemical vapor deposition is 700°C to 1200°C.
[0082] In a third aspect of the embodiment of the present application, there is provided an electrode plate, the electrode plate comprising the silicon carbon composite material of the first aspect or obtained through the preparation of the second aspect.
[0083] The electrode plate in this embodiment of the present application may be a positive electrode plate or a negative electrode plate.
[0084] Using a negative plate as an example, in a possible implementation, the silicon carbon composite material, the conductive additive, the binder, etc. are added to a solvent for stirring and dispersing to obtain a negative electrode slurry, and then the negative electrode slurry is coated on at least one side of a negative electrode current collector (usually a copper foil), the negative electrode slurry is dried, and the negative electrode slurry is converted into a negative electrode active layer to obtain the negative electrode plate of this embodiment of the present application. For example, the conductive additive may be selected from (but is not limited to) at least one of super-P, conductive carbon black, carbon nanotube, and acetylene black, the binder may be selected from (but is not limited to) one of polyvinylidene fluoride (PVDF) or polyethylene oxide (PEO), and the solvent may be distilled water.
[0085] The silicon carbon composite material of the first embodiment or the silicon carbon composite material prepared in the second embodiment has high energy density, excellent structural stability and electrical conductivity. Therefore, the negative electrode active layer of the electrode plate does not easily fall off from the surface of the current collector and has excellent electrical conductivity, which not only improves the energy density of the secondary battery, but also ensures the cycle performance, rate performance and high-speed charging performance of the secondary battery.
[0086] In a fourth aspect of the embodiment of the present application, there is provided a secondary battery, the secondary battery including the electrode plate of the third aspect.
[0087] The secondary battery of this embodiment of the present application includes the above-mentioned electrode plate, so that the energy density, cycle performance, rate performance and fast charging performance are greatly improved. The secondary battery can be, for example, a lithium ion battery or a sodium ion battery.
[0088] For example, the electrode plate is a negative plate. In addition to the negative plate, the secondary battery of this embodiment of the present application further includes a positive plate, a separator and an electrolyte.
[0089] In a possible implementation, the positive plate includes a positive active layer disposed on at least one side of a positive current collector (usually an aluminum foil). In particular, after at least one side of the positive current collector is coated with a positive slurry, the solvent in the positive slurry is dried to obtain a positive plate. The positive slurry includes at least a positive active material, a conductive additive, a binder, and a solvent. For example, the positive electrode active material may be selected from, but is not limited to, at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate; the conductive additive may be selected from, but is not limited to, at least one of super-P, conductive carbon black, carbon nanotubes, and acetylene black; the binder may be selected from, but is not limited to, one of polyvinylidene fluoride (PVDF) or polyethylene oxide (PEO); and the solvent may be N-methyl-2-pyrrolidone (NMP).
[0090] In a possible implementation, the separator may be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylenedifluoride.
[0091] In a possible implementation, the electrolyte includes at least an organic solvent and a lithium salt, the organic solvent may be selected from ethylene carbonate, 2,3-butylene carbonate, propylene carbonate, ethyl methyl carbonate, vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, ethyl methyl fluorocarbonate, difluoroethylene carbonate, dimethyl fluorocarbonate, dimethyl carbonate, diethyl carbonate, and dipropyl carbonate, and the lithium salt may be lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium The sulfuric acid may be selected from at least one of bis(trifluoromethanesulphonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI).
[0092] In a fifth aspect of the present embodiment, there is provided an electronic device, wherein a driving source or an energy storage unit of the electronic device is the secondary battery of the fourth aspect.
[0093] Since the electronic device of this embodiment of the present application uses the above-mentioned secondary battery as a driving source or energy storage system, the battery life and the electronic device life are excellent, and the user satisfaction is high.
[0094] The electronic devices may include, but are not limited to, mobile or fixed terminals that have batteries, such as mobile phones, tablet computers, notebook computers, ultra-mobile personal computers (UMPCs), handheld computers, walkie-talkies, netbooks, point-of-sale machines, personal digital assistants (PDAs), wearable devices, and virtual reality devices.
[0095] In this embodiment of the present application, a mobile phone 100 is used as an example of the above electronic device for description. The mobile phone 100 may be a foldable mobile phone 100 or a bar-type mobile phone 100. In this embodiment of the present application, the bar-type mobile phone 100 is used as an example. FIGS. 1 and 2 show the structure of the mobile phone 100. Referring to FIGS. 1 and 2, the mobile phone 100 may include a display 10, a rear housing 60, a metal intermediate frame 50, a circuit board 30, and a secondary battery 40 between the display 10 and the rear housing 60. The display 10 is disposed on one side of the metal intermediate frame 50, and the rear housing 60 is disposed on the other side of the metal intermediate frame 50.
[0096] The display 10 may be an Organic Light-Emitting Diode (OLED) display or a Liquid Crystal Display (LCD). The rear housing 60 may be a metal rear housing 60, a glass rear housing 60, a plastic rear housing, or a ceramic rear housing 60. The material of the metal mid-frame 50 may be a magnesium alloy or an aluminum alloy.
[0097] It should be noted that in this embodiment of the present application, the material of the metal intermediate frame 50 includes (but is not limited to) an intermediate frame made of a metal material such as magnesium alloy, aluminum alloy, titanium alloy, etc., and alternatively, the metal intermediate frame 50 can be a non-metal intermediate frame made of a material such as ceramic. The materials of the display 10, the rear housing 60 and the metal intermediate frame 50 are specifically set based on the actual use, and the present embodiment is not limited thereto.
[0098] The metal intermediate frame 50 may include a metal intermediate plate 53 and a metal frame 52 disposed on the outer periphery of the lower frame. The metal frame 52 may include an upper frame and a lower frame disposed opposite each other, and two side frames located between the upper frame and the lower frame. The metal frame 52 and the metal intermediate plate 53 may be connected by welding, caulking, or integral formation.
[0099] The circuit board 30 and the secondary battery 40 can be disposed on the metal intermediate plate 53 of the metal intermediate frame 50. For example, the circuit board 30 and the secondary battery 40 may be disposed on one side of the metal intermediate plate 53 facing the rear housing 60, or the circuit board 30 and the secondary battery 40 may be disposed on one side of the metal intermediate plate 53 facing the display 10. When the circuit board 30 is disposed on the metal intermediate plate 53, an opening may be provided in the metal intermediate frame 50, and elements of the circuit board 30 may be placed in the opening of the metal intermediate frame 50.
[0100] The circuit board 30 may be a printed circuit board (PCB), and a heat dissipation element 31 is disposed on the circuit board 30. The heat dissipation element 31 may be a master chip of an electronic device, such as a power amplifier, an application processor (Central Processing Unit, CPU), a power management IC (PMIC), or a high-frequency IC.
[0101] The secondary battery 40 may be connected to a charge management module (not shown) and the circuit board 30 using a power management module. The power management module receives input from the secondary battery 40 and / or the charge management module and provides power to the processor, the internal memory, the external memory, the display 10, the camera, the communication module, etc. The power management module may be further configured to monitor parameters such as the capacity of the secondary battery 40, the cycle count of the secondary battery 40, and the health status (leakage and impedance) of the secondary battery 40. In other embodiments, the power management module may alternatively be located in the processor of the circuit board 30. In other embodiments, the power management module and the charge management module may alternatively be located in the same component.
[0102] It is understood that the structure shown in this embodiment of the present application does not constitute a particular limitation on the mobile phone 100. In other embodiments of the present application, the mobile phone 100 may include more or fewer components than those shown in the figures, some components may be combined, some components may be separated, or there may be a different component layout. The components shown in the figures may be implemented in hardware, software, or a combination of software and hardware.
[0103] In the description of the embodiments of the present application, it should be noted that unless otherwise specified and limited, the terms "installation", "connection to" and "connection" should be interpreted in a broad sense. For example, the connection may be a fixed connection, an indirect connection using an intermediate medium, an internal connection between two elements, or an interactive relationship between two elements. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application based on the specific circumstances.
[0104] Hereinafter, the silicon carbon composite material and the secondary battery according to the embodiments of the present application will be described in detail using specific embodiments.
[0105] EMBODIMENT 1 The silicon carbon composite material of this embodiment is prepared according to the following method.
[0106] (1) Measure out 30 ml of deionized water and place the deionized water in a water bath under isothermal reaction conditions at 85°C. Add 0.5 ml of trimethoxysilane to the deionized water and stir for 10 minutes to obtain an aqueous solution of trimethoxysilane.
[0107] Under stirring conditions, 0.2 ml of ammonia water (25% by weight to 28% by weight) is added to the aqueous solution of trimethoxysilane to adjust the pH of the system to 8 to 9, promoting hydrolysis to form a white emulsion, and stirring is continued for 3 hours. After that, suction filtration is performed to obtain a solid product, which is washed with alcohol and dried to obtain a spherical trimethoxysilsesquioxane precursor.
[0108] (2) The spherical trimethoxysilsesquioxane precursor is placed in a tubular furnace, and the temperature rise rate is set to 10°C / min, and the material is kept at 1000°C for 5 hours under argon protective atmosphere. When the period of keeping reaches 4.5 hours, a gas flow of 100 sccm of methane / hydrogen gas mixture (10%vol.:90%vol.) is fed, and the gas feeding is stopped after 0.5 hours. When the tubular furnace is naturally cooled to below 100°C, the material, i.e., the silicon carbon composite material of this embodiment, is taken out.
[0109] Figure 3a is a schematic diagram of the overall morphology and microstructure of the silicon carbon composite material according to embodiment 1 of the present application. From Figure 3a, it can be seen that the silicon carbon composite material of embodiment 1 is a microsphere with a uniform size distribution and a diameter of about 300 nm.
[0110] 3b is a high-resolution HAADF phase diagram of a cross-section of a fractured area of the silicon carbon composite according to embodiment 1 of the present application. From FIG. 3b, it can be seen that the internal structure of the silicon carbon composite has worm-shaped SiO x It can be seen that the nanoparticles (light areas) are distributed throughout the continuous carbon matrix (dark areas).
[0111] Figure 3c is a TEM image of the silicon carbon composite according to embodiment 1 of the present application. Figure 3d is an enlarged view of a portion of the coating layer in Figure 3c. As shown in Figure 3c, there is a carbon coating layer (above the dashed line) on the surface of the silicon carbon composite, and the coating layer is regularly arranged graphitized carbon. In addition, in Figure 3d, d002 is 0.336 nm, and the thickness of the coating layer is 10 nm.
[0112] FIG. 3e is a STEM image of the silicon carbon composite material according to embodiment 1 of the present application. FIG. 3f to FIG. 3h are SEM images of EELS surface scan of the silicon carbon composite material according to embodiment 1 of the present application. Clear graphitized carbon streaks can be observed from FIG. 3e, and the corresponding EELS surface scan SEM images of FIG. 3f to FIG. 3h indicate that a graphitized carbon layer is generated on the surface of the material. In FIG. 3f, the area below the dashed line is shown in green and the area above the dashed line is shown in black, indicating that the silicon element in the material is uniformly distributed. FIG. 3g shows the verification of carbon element throughout the particle. The area below the dashed line is shown in red and the area above the dashed line is shown in black, indicating that there are two forms of carbon element in the material: carbon element uniformly distributed in the particle and carbon layer covering the surface of the particle. Figure 3h can be understood as a composite of Figures 3f and 3g, and shows that there is indeed a carbon coating layer on the surface of the particle, and a structure in which silicon and carbon are uniformly distributed inside the particle.
[0113] FIG. 4 is a spectrum of the 29Si magic angle spinning nuclear magnetic resonance (MAS NMR) technique of the silicon carbon composite material according to embodiment 1 of the present application. Chemical displacement 78.0 cm-1 The characteristic peak located at is a Si-C peak, with a chemical displacement of 111.0 cm -1 The chemical displacement for the Si-O(3) peak intensity I(Si-O) is 78.0 cm -1 It can be seen that the ratio of the peak intensity I(Si-C) of Si-C belonging to the above group satisfies the relationship I(Si-C) / I(Si-O)<0.05.
[0114] The silicon carbon composite material of embodiment 1 was etched using hydrogen fluoride to remove SiO x is etched away, leaving 15 wt% of the carbon substrate. Figure 5a is a TEM image of the carbon substrate obtained after etching the silicon carbon composite material according to embodiment 1 of the present application. As shown in Figure 5a, the carbon substrate is continuously distributed and has a multi-channel structure, and the carbon substrate is a continuously dispersed carbon network structure. Figure 5b is a Raman spectrogram of the carbon substrate obtained after etching the silicon carbon composite material according to embodiment 1 of the present application. As shown in Figure 5b, the graphitization degree of the carbon substrate is high, with ID / IG=0.9.
[0115] Before and after the silicon carbon composite material of embodiment 1 is etched, the specific surface area of the silicon carbon composite material before etching and the specific surface area of the carbon substrate after etching are verified by nitrogen adsorption and desorption method. Figure 5c shows the N2 adsorption and desorption curves of the silicon carbon composite material of embodiment 1 of the present application before and after etching. Figure 5d shows the N2 adsorption and desorption aperture distribution curves of the silicon carbon composite material of embodiment 1 of the present application before and after etching. According to the BET adsorption isotherm, the specific surface area of the silicon carbon composite material before etching is 10 m 2 / g, and the specific surface area of the carbon substrate after etching is up to 1200 m 2 / g.
[0116] In addition to the above, the carbon substrate after etching is verified by CO2 adsorption and desorption. Figure 5e is the CO2 aperture distribution curve of the carbon substrate obtained after etching the silicon carbon composite material according to embodiment 1 of the present application. It can be seen that the white holes with sizes of 0.3 nm to 0.9 nm are abundant in the carbon substrate in the gray area in the upper right corner, and the size of the white holes is SiO x corresponds to the size of the particle.
[0117] 5f is an XPS spectrogram of the silicon carbon composite material according to the first embodiment of the present application. From FIG. 5f, it can be seen that the silicon oxide in the silicon carbon composite material of the present embodiment is specifically SiO 1.48 It can be seen that.
[0118] EMBODIMENT 2 The silicon carbon composite material of this embodiment is prepared according to the following method.
[0119] (1) Measure out 50 ml of deionized water, add 1.0 ml of 3-1-[3-(trimethoxysilyl)propyl]urea to the deionized water, and stir at standard temperature for 30 minutes to obtain an aqueous solution of 3-1-[3-(trimethoxysilyl)propyl]urea.
[0120] Under stirring conditions, 0.5 ml of aqueous ammonia (25% to 28% by weight) is added to the aqueous solution of 3-1-[3-(trimethoxysilyl)propyl]urea to adjust the pH of the system to approximately 9, promoting hydrolysis to form a white suspension. After continuing to stir for 24 hours, the mixture is suction filtered and dried to obtain a spherical ureidopropyltrimethoxysilsesquioxane precursor.
[0121] (2) The ureidopropyltrimethoxysilsesquioxane precursor is placed in a tubular furnace, the temperature is increased at a rate of 5°C / min, and the furnace is heated to 1000°C for 8 hours under an argon protective atmosphere. After the furnace is naturally cooled to less than 100°C, the material, i.e., the silicon carbon composite material of the present embodiment, is taken out.
[0122] Figure 6 is a schematic diagram of the overall morphology and microstructure of the silicon carbon composite material according to embodiment 2 of the present application. From Figure 6, it can be seen that the silicon carbon composite material of embodiment 2 is a microsphere with a uniform size distribution and a diameter of about 1 μm.
[0123] Comparative Example 1 Comparative Example 1 is a commercially available silicon oxygen carbon anode material. FIG. 7a is a SEM diagram of the morphology of the silicon oxygen carbon anode material according to Comparative Example 1 of the present application. FIG. 7b is a TEM diagram of the inside of the silicon oxygen carbon anode material according to Comparative Example 1 of the present application. As shown in FIG. 7a, the silicon oxygen carbon anode material of Comparative Example 1 is an irregular block, with a D50 size of 5 μm-6 μm. From FIG. 7b, it can be seen that in the internal structure of the silicon oxygen carbon anode material of Comparative Example 1, nano silicon oxygen particles with a size of 5 nm are dispersed in the carbon substrate.
[0124] Comparative Example 2 The silicon carbon composite material of this comparative example is prepared according to the following method.
[0125] (1) Measure out 1 mL of aqueous ammonia, disperse the aqueous ammonia in a mixed solution of 20 mL of water and 10 mL of ethanol, stir the solution for 1 hour, add 1 mL of vinyltriethoxysilane, and stir the solution at room temperature for 5 hours to obtain a milky solution.
[0126] The milky solution is transferred to a polytetrafluoroethylene lining and subjected to a hydrothermal process at 100°C for 12 hours, followed by centrifugation and washing the solid phase system with deionized water and ethanol three times separately, after which the solid phase system is placed in a drying box at 70°C for 12 hours.
[0127] (2) Put a certain amount of the above product into a quartz ceramic boat, place the quartz ceramic boat into a tubular atmospheric furnace used for calcination, set the temperature increase rate at 5°C / min, and keep at 800°C for 45 minutes under argon protective atmosphere to finally obtain the silicon carbon composite material of Comparative Example 2.
[0128] FIG. 8a is a high-resolution HAADF phase diagram of a cross section of the fractured area of a silicon carbon composite according to Comparative Example 2 of the present application, in which SiO x The particle size exceeds 5 nm.
[0129] The silicon carbon composite material of Comparative Example 2 is etched using hydrogen fluoride. Figure 8b is a TEM image of the carbon substrate obtained after etching the silicon carbon composite material of Comparative Example 2. As shown in Figure 8b, the etched carbon substrate is divided into several parts and distributed discontinuously.
[0130] FIG. 9 shows the spectrum of the silicon carbon composite material according to Comparative Example 2 by the magic angle spinning nuclear magnetic resonance (MAS NMR) technique, in which I(Si-C) / I(Si-O) is clearly greater than I(Si-C) / I(Si-O) of the first embodiment.
[0131] Verification example 1. The silicon carbon materials of the first and second embodiments and the first and second comparative examples were compressed to about 1.7 g / cm by the action of a mercury intrusion device. 3 The compacted powder is packed into a sheet with a density of 10 ...
[0132] 2. The silicon carbon materials of the first and second embodiments and the first and second comparative examples are mixed with graphite in a specific ratio, so that the gram capacity is unified to 500mAh / g, and the mixture is assembled with metallic lithium into a button half battery.
[0133] Active materials (silicon carbon material and graphite), acetylene black and sodium alginate are dispersed in deionized water in a mass ratio of 70:20:10, the solution is stirred uniformly and ultrasonicated for 4 hours to obtain an electrode slurry. The obtained electrode slurry is coated on the surface of copper foil and dried at 85°C to obtain a positive electrode plate. LiPF 1M is dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) is used as the electrolyte, lithium plate is used as the negative electrode, Celgard 2400 is used as the separator, CR 2025 stainless steel is used as the battery housing, and assembled to obtain a button lithium-ion battery.
[0134] The cycle life and rate performance of the battery are verified. The verification method is as follows. See Table 1 for the results.
[0135] Cycle life The charge and discharge cycle verification is performed on the battery at 25°C using a battery charge and discharge tester, and the battery is charged and discharged at a constant current within the voltage range of 0.01V to 0.3V. As the battery cycles, the battery capacity is continuously attenuated. The number of cycles that the battery goes through until the capacity is attenuated to 80% of the initial discharge capacity is recorded as the cycle life of the battery.
[0136] b. Rate performance The charge and discharge cycle verification is carried out on the battery at 25°C using a battery charge and discharge tester, the battery is charged and discharged at a constant current within the voltage range of 0.01V to 0.3V. After a certain number of cycles each time, the current density is changed and the cycle continues. The capacity released by the battery performance under various current densities is verified.
[0137] [Table 1]
[0138] The following can be seen from Table 1:
[0139] 1. The electrical conductivity of the first and second embodiments is obviously superior to that of the first and second comparative examples. Therefore, the silicon carbon composite of the first and second embodiments can effectively improve the fast charging performance of the secondary battery. The reason is that the carbon layer of the first comparative example mainly covers the outer surface of the material, which does not form an effective path for the lithium ions to transfer to the silicon oxygen particles, and the particle size of the silicon oxygen particles is large. Therefore, the lithium ion transfer efficiency is not high. As a result, the electrical conductivity is low. There are many Si-C bonds in the second comparative example. Therefore, the electrical conductivity of the carbon substrate is affected. As a result, the electrical conductivity is low.
[0140] The electrical conductivity of the embodiment 2 is superior to that of the embodiment 1. This is because the silicon carbon composite material of the embodiment 2 is doped with a different element, which greatly improves the electrical conductivity.
[0141] 2. The cycle performance of the secondary battery obtained by using the materials of the first and second embodiments is obviously superior to that of the secondary battery obtained by using the materials of the first and second comparative examples. The reason is that the size of the silicon-oxygen particles of the material of the first comparative example is 5 μm-6 μm, and the size of the silicon-oxygen particles of the material of the second comparative example is over 5 nm. Therefore, the volume expansion in the cycle process is large, and the crushing of the silicon-oxygen particles occurs easily. As a result, the cycle performance of the battery is affected.
[0142] 3. The rate performance of the secondary battery obtained using the materials of the embodiments 1 and 2 is obviously superior to that of the secondary battery obtained using the materials of the comparative examples 1 and 2. The reason is that the electrical conductivity of the materials of the comparative examples 1 and 2 is poor, and therefore the capacity of the battery cannot be effectively released. As a result, the rate performance of the secondary battery obtained using the materials of the comparative examples 1 and 2 is poor, and especially when the current density is high, only a small capacity of the battery is released.
[0143] Finally, it should be noted that the above embodiments are only intended to describe the technical solutions of the embodiments of the present application, rather than limiting the embodiments of the present application. Although the embodiments of the present application have been described in detail with respect to the above embodiments, those skilled in the art will naturally understand that, without departing from the scope of the technical solutions of the embodiments of the present application, they can still modify the technical solutions described in the above embodiments, or make equivalent substitutions for some or all of the technical features thereof. [Explanation of symbols]
[0144] 1 Current collector 2 Electrode active material 3. Conductive materials 4. Binder 10. Display 30 Circuit Board 31 Heat dissipation element 40 Lithium-ion battery 50 Metal intermediate frame 52 Metal intermediate plate 53 Metal Frame 60 Rear housing 100 Mobile Phones
Claims
1. A silicon carbon composite material comprising a core and a carbon coating layer, at least a portion of a surface of the core being covered by the carbon coating layer; The core is made of a carbon substrate and SiO x particles, the carbon substrate having N channels continuously distributed and communicating with the outside, the SiO x Particles are loaded into the channel; The SiO x A silicon carbon composite material, the particles having a size of 0.1 nm to 0.9 nm, 0.9≦x≦1.7, and N≧1, where N is an integer.
2. 2. The silicon carbon composite material of claim 1, wherein the mass percentage content of the carbon substrate is 10% to 40% based on the mass of the core.
3. The specific surface area of the carbon substrate is 800 m 2 / g~1400m 2 3. The silicon carbon composite material according to claim 1, wherein the silicon carbon composite material has a molecular weight of 1.0 to 1.0 g.
4. The specific surface area of the silicon carbon composite material is 5 m 2 / g to 20m 2 / g.
5. 4. The silicon carbon composite of claim 3, wherein 1.5 > ID / IG > 0.8 in a Raman spectrogram of the carbon substrate.
6. The nuclear magnetic resonance spectrum of the silicon carbon composite material comprises a Si—C peak and a Si—O peak, and the intensity I Si-O The intensity of the Si-C peak I Si-C The silicon carbon composite of claim 1 , wherein the ratio of is less than 0.
05.
7. 2. The silicon carbon composite material according to claim 1, wherein the carbon coating layer has a thickness of 5 nm to 20 nm, and the carbon atom interlayer spacing d002 of the carbon coating layer is 0.3354 nm to 0.34 nm.
8. 8. The silicon carbon composite of claim 1 , further comprising at least one of the elements N, P, B, Cl, Br and I.
9. The silicon carbon composite of claim 1, wherein the grain size of the silicon carbon composite is between 50 nm and 2 μm.
10. 1. A method for preparing a silicon carbon composite material, comprising the steps of: (1) stirring an aqueous solution of trimethoxysilane compound under alkaline conditions to make the system turbid, and collecting precursor particles; (2) performing a sintering process on the precursor particles to obtain the silicon carbon composite material, the temperature of the sintering process being 900°C to 1200°C, and the duration of the sintering process being 1 hour to 10 hours; After step (1), the method further comprises providing a carbon source within the system for carbon coating; The silicon carbon composite material comprises a core and a carbon coating layer, at least a portion of a surface of the core is covered with the carbon coating layer, The core is made of a carbon substrate and SiO x particles, the carbon substrate having N channels communicating with the outside, the SiO x Particles are loaded into the channel; The SiO x The method, wherein the size of the particles is between 0.1 nm and 0.9 nm, and 0.9≦x≦1.
7.
11. The preparation method according to claim 10, wherein in step (1), 25% by weight to 28% by weight of ammonia water is added to the aqueous solution of trimethoxysilane compound so that the pH of the system is 8 to 13.
12. The preparation method according to claim 10, wherein in the aqueous solution of trimethoxysilane compound, the volume concentration of the trimethoxysilane compound is 0.4% to 5%.
13. The preparation method according to claim 10, wherein the temperature increase rate of the sintering process is 1°C / min to 10°C / min.
14. The preparation method according to claim 10, wherein the carbon coating is carried out using a deposition reaction, the temperature of the deposition reaction being between 700°C and 1200°C.
15. 11. The method of claim 10, wherein the trimethoxysilane compound is selected from one or more of trimethoxysilane, methyltrimethoxysilane, N-trimethoxypropylsilane, N-trimethoxyoctylsilane, 3-aminopropyltrimethoxysilane, 3-1-[3-(trimethoxysilyl)propyl]urea, N-dodecyltrimethoxysilane, (3-chloropropyl)trimethoxysilane, (3-phobylpropyl)trimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, trimethoxybenzenesilane, vinyltrimethoxysilane, and 3-iodophenyltrimethoxysilane.
16. 10. An electrode plate comprising the silicon carbon composite material of any one of claims 1 to 9.
17. A secondary battery comprising the electrode plate according to claim 16.
18. An electronic device, the power source or energy storage source of the electronic device comprising the secondary battery according to claim 17.
Citation Information
Patent Citations
Core-shell structure, manufacturing method thereof, composition for negative electrode using the core-shell structure as negative electrode active material, negative electrode, and secondary battery
JP2020001941A